2017
DOI: 10.33474/jpm.v3i2.647
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Tes Online Menggunakan Thatquiz Pada Bidang Studi Matematika

Abstract: Pelaksanaan Ujian Nasional Berbasis Komputer (UNBK) di SMP dan SMA tahun 2016 di Indonesia adalah langkah awal Pendidikan kita menuju Digitalisasi Teknologi dan Informasi dalam meningkatkan kualitas pendidikan khususnya dalam pelaksanaan Ujian Nasional. Damapaknya seorang guru benar-benar dituntut profesionalismenya untuk meningkatkan kemampuan dalam bidang Teknologi untuk mengikuti arus perkembangan teknologi, khusunya dalam menyelenggarakan tes berbasis komputer baik offline maupun online. Tidak semua guru m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In terms of information and communication, correspondence and administration, as well as testing, digitization has been carried out for the past few years. A number of studies such as Retnawati et al [9], Alifiani et al [10], have reported how the constraints and efficacy of digitization of education on these aspects. However, digitization in the aspect of learning is still not popularly implemented both at the higher education level, especially in primary and secondary education.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of information and communication, correspondence and administration, as well as testing, digitization has been carried out for the past few years. A number of studies such as Retnawati et al [9], Alifiani et al [10], have reported how the constraints and efficacy of digitization of education on these aspects. However, digitization in the aspect of learning is still not popularly implemented both at the higher education level, especially in primary and secondary education.…”
Section: Introductionmentioning
confidence: 99%